2019
DOI: 10.1111/jdv.15618
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of atopic dermatitis in children aged 1–12 months: elaboration of novel diagnostic criteria for infants in China and estimation of prevalence

Abstract: Background Atopic dermatitis (AD) is the most common skin disorder in infancy. However, the diagnosis and definite significance of infantile AD remains a debated issue. Objective To analyse the phenotypes of AD in infancy, to establish diagnostic criteria and to estimate the prevalence of this condition in China. Methods This is a multicentric study, in which 12 locations were chosen from different metropolitan areas of China. Following careful and complete history‐taking and skin examination, the definite dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In 2017, the estimated number of new patients with AD was 27 million, ranking second among the three types of dermatitis ( James et al., 2018 ). The prevalence of AD may vary by race: in the USA, the prevalence among whites (11%) is lower than that among African Americans (17%) ( Kim et al., 2019 ; Wan et al., 2019 ); the prevalence of AD in infancy in China is as high as 30.48% ( Guo et al., 2019 ); and the incidence and persistence of AD are higher in certain non-white racial/ethnic subgroups than in non-Hispanic whites ( Kim et al., 2019 ). Although the mortality rate for AD is very low, some studies report that the long-term risk of atrial fibrillation in AD patients increases by 20% ( Schmidt et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, the estimated number of new patients with AD was 27 million, ranking second among the three types of dermatitis ( James et al., 2018 ). The prevalence of AD may vary by race: in the USA, the prevalence among whites (11%) is lower than that among African Americans (17%) ( Kim et al., 2019 ; Wan et al., 2019 ); the prevalence of AD in infancy in China is as high as 30.48% ( Guo et al., 2019 ); and the incidence and persistence of AD are higher in certain non-white racial/ethnic subgroups than in non-Hispanic whites ( Kim et al., 2019 ). Although the mortality rate for AD is very low, some studies report that the long-term risk of atrial fibrillation in AD patients increases by 20% ( Schmidt et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of AD in China has been increasing rapidly during the past two decades, 13 which is approaching Western countries and developed Asia countries such as Japan 14 and Korea 15 . Previously, most of the interests have been placed in infantile and childhood AD in China, 16,17 and adult AD has also been investigated for diagnosis criteria and clinical features 18 ; however, elderly AD is far less recognized and explored. The present study demonstrated for the first time the unique clinical features and distinct endotype of elderly AD patients in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the prevalence of AD has been increasing globally, with prevalence rates ranging from 10% to 20% in children in developed countries. [1] The overall prevalence of AD in children in China is also on a continuous rise, with prevalence rates of 3.07%, [3] 8.3%, [4] and 12.94% [5] investigated in 2002, 2010, and 2014, respectively, The 2019 survey showed a prevalence of 40.81% [6] in 3-month-old infants. It is generally believed that the prevalence of AD decreases with age and the incidence is lower in rural areas.…”
Section: Introductionmentioning
confidence: 99%